THE ABILITY OF THE SECOND YEAR STUDENTS OF THE STATE ISLAMIC SENIOR HIGH SCHOOL (MAN) 1 PEKANBARU IN COMPREHENDING RECOUNT TEXTS - Afrizan, Awi; Supriusman, Supriusman; Mahdum, Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research was aimed to find out the Ability of the Second Year Students of the State Islamic Senior High School (MAN) 1 Pekanbaru in Comprehending Recount Texts. The population of this research was the Second Year Students of the State Islamic Senior High School (MAN) 1 Pekanbaru. The number of sample was 30 students selected by using cluster random sampling technique. The research instrument was multiple choice questions consisted 40 questions. The test was given by using eight components of reading comprehension and recount texts such as main idea, factual information, meaning of difficult word, reference, inference, social function of recount text, generic structures of recount text and language features of recount text. The data were analyzed by classifying them into four levels of ability, such as poor, average, good, and excellent. The result showed that the ability of the second year students of the State Islamic Senior High School (MAN) 1 Pekanbaru was at good level with mean score was 66.1.Key Words: Students’ ability, Reading comprehension, Recount text